THE GEODYNAMIC SETTING OF THE NAIN OPHIOLITES; CENTRAL IRAN: EVIDENCE FROM CHROMIAN SPINELS IN THE CHROMITITES AND ASSOCIATED ROCKS - Ghazi, Javad Mehdipour; Moazzen, Mohssen; Rahghoshay, Mohammad; Moghadam, Hadi Shafaii (Ofioliti, 2011)
In central Iran; to the northwest of the Central Iranian micro-continental (CIM) block; the coloured mélange is characterized by widespread ophiolite blocks. In the Nain area; these ophiolite blocks; known as Nain ophiolites; are mainly composed of mantle peridotites. Based on field and petrographic observations and on the chemistry of Cr-spinels; two types of chromitites have been recognized in the Nain ophiolites. The first type occurs as chromitite patches within the harzburgites. The Cr number [Cr# = 100*Cr/(Cr+Al)] of the Cr-spinels varies between 58 and 63 in chromitite patches and 39-40 in harzburgites. Calculated amount of Al2O3 and ratio of FeO/MgO in the parental melts of the chromitite patches indicate a boninitic melts for the source magmas of the Cr-spinels. The REE patterns for the studied harzburgites and lherzolites are similar to those from abyssal peridotites. These characteristics suggest a back-arc basin setting for the generation of the chromitite patches as well as of the harzburgites and lherzolites from the Nain ophiolites. The second type of chromitites occurs as lenses (chromitite pods) in dunites. The Cr number of Cr-spinels of these chromitites varies between 69 and 73. The Cr-spinels of these chromitites also show a boninitic nature for the parental melts. These characteristics of chromitite lenses show that they were generated at an arc setting. Therefore; intra-oceanic subduction in the Nain basin in Early Cretaceous can be proposed on the basis of these data on the origin of the chromitite lenses. Intra-oceanic rifting in a back-arc setting generated an oceanic back-arc basin in the Nain area in Late Cretaceous.; The chromitite patches and the studied harzburgites and lherzolites were likely formed in the mantle beneath the back-arc basin. On the whole; the field and petrographic observations as well as the degree of partial melting; calculated on the basis of the Cr#; suggest that the genesis of these rocks can be explained according to a mixed open-channel cumulate/rock-reaction model.